A rectification strategy in genetic algorithms for academic timetabling problem - Teoh, Chong Keat; Wibowo, Antoni; Ngadiman, Salihin (Penerbit UTM Press, 2015)
The university course timetabling problem is both an NP-hard and NP-complete scheduling problem.The nature of the problem concerns with the assignment of lecturers-courses to available teaching space in an academic institution and may take on the form of high school timetabling, examination timetabling or university course timetabling. In this paper, the authors attempt to construct a feasible timetable for a faculty department in a local university in Malaysia which at the present moment; the scheduling task is performed manually by an academic registrar. The feasible timetable is constructed by means of Genetic Algorithm, embedded with a rectification strategy which transforms infeasible timetables into feasible timetables.